Hezekiah and the Assyrian Spies : reconstruction of the Neo-Assyrian Intelligence Services and its Significance for 2 Kings 18-19. - Dubovský, Peter, S.I., 1921-2008 (Biblica et orientalia (Editrice Pontificio Istituto Biblico), 2006)
Among the well-preserved ancient archives in Niniveh and Nimrud there are many cuneiform tablets which reveal the existence of secret service networks used by the Assyrian court to communicate with provincial officials during the 8th and the 7th century B.C. Using this vast material the author shows in great detail how the Assyrians collected, transmitted, and double-checked sensitive information. This study also includes an in-depth analysis of the activities of the Assyrian espionage involved in Sennacherib's invasion of Judah described in 2 Kgs 18-19. This fascinating book casts new light on the political situation and intrigues reflected in the biblical passage. Peter Dubovsky studied biblical exegesis at the Pontifical Biblical Institute (SSL., 1999) and at Harvard Divinity School (Th. D., 2005). Currently he teaches old testament exegesis and hebrew at the Theological Faculty of Trnava University in Bratislava.